Challenges and Responses in Tunisian Activism a Study of Tunisian Social Movements in the Post Revolutionary Period - ZOUAOUI, SARRA (İstanbul Kültür Üniversitesi, 2023)
This thesis analyzes the development of Tunisian activism in the post the 2011 period, focusing on the challenges facing social movements in the country. This study examines the history of Tunisian activism from colonial rule to the present day, with a particular emphasis on the post-revolution period. Drawing on existing literature and theory, the study identifies the emergence of new forms of digital activism and transnational networks and the fragmentation of social movements into multiple competing organizations as key features of post-revolutionary Tunisian activism. Building on this analysis, the study develops a specific hypothesis that the Tunisian state's response to post-revolutionary Tunisian activism, including co-optation and repression, has created significant challenges for social movements in sustaining mobilization and achieving substantive social and political change. This hypothesis is tested by examining the state's response to activist mobilization, including its use of media and surveillance, as well as analyzing the challenges faced by social movements, such as generational divides and the difficulties of coordinating across organizations. The study concludes by reflecting on the implications of these findings for the future of Tunisian activism and the broader implications for social movements in the Middle East and North Africa. Ultimately, this thesis contributes to a deeper understanding of the complexities of post-revolutionary politics in Tunisia and the challenges activists face to build a more just and democratic society.
Tunus Aktivizmindeki Zorluklar ve Cevaplardevrim Sonrası Dönemde Tunus Toplum Hareketleri Üzerine Bir İnceleme
▪ Yüksek lisans tezi.
Keywords: Social Movements theories; Tunisia; Democratic Transition; Activism; Civil Society